Case report: Anti-CNTN1 antibody-associated nodopathies disease with asymmetric onset - Li, Qian; Chen, Qing; Zhang, Ting; Xu, Ying; Kan, Yanmin; Zhang, Jing (Frontiers in Neurology, 2023)
Anti-contactin-1 (CNTN1) IgG4 antibody-associated nodopathies is an autoimmune antibody-mediated peripheral neuropathy with a unique clinical presentation, pathophysiology, electrophysiology, and therapeutic response. The critical histopathological features are a dense lymphoplasmacytic infiltrate, a storiform pattern of fibrosis, and obliterative phlebitis. Here, a 62-year-old male patient presented with subacute unilateral limb onset, progressive exacerbation, marked weakness of the extremities, cranial, and autonomic nerve involvement. Neurophysiology showed slowed motor nerve conduction velocity (MCV), prolonged distal motor delay (DML), slowed sensory nerve conduction velocity (SCV), decreased sensory nerve activity potential (SNAP) amplitude, decreased amplitude of bilateral neuromotor conduction, abnormal cutaneous sympathetic response (SSR) in both lower extremities, axonal damage, prolonged F-wave latency, and discrete waves. In the initial phase, there was a response to intravenous immunoglobulin (IVIG), and corticosteroids and rituximab were also effective. After 1 year follow-up, the patient improved significantly. This article reports on a patient with nodular disease with anti-contactin-1 (CNTN1) IgG4 antibodies and reviews the literature to improve clinicians' understanding of the disease.